Sunan Kalijaga and Diplomacy For Peace In Perspective Suluk Linglung Sunan Kalijaga - Zarkasi, Fatchullah (Journal Of Middle East and Islamic Studies, 2024)
This research aims to find out more about Sunan Kalijaga, a historical actor in the spread of religion and culture on the island of Java in the 15th and 16th centuries, is also known as an accomplished diplomat for understanding around. We can know how to spread and understand culture and religion by using the right tools. This does not mean avoiding violent conflict, but conflict can be minimized and managed with good management. This research uses a hermeneutic approach, namely reading, understanding and relating. The data contained in the Suluk Linglung Manuscript was then developed and clarified to form a complete and strong theoretical combination, as in the contents of the Suluk Linglung which the author considers implicitly and explicitly to be the basis and teachings about Sunan Kalijaga's diplomacy. Until now we can see the results of culture, teachings, ideology and art, such as dance, sculpture, painting, building art, music art in the form of songs, from Sunan Kalijaga and so on. And what is no less important is the teaching of moderation in practicing and practicing religion as well.